Severe polyhydramnios as neonatal presentation of Bartter’s syndrome type IV - Coroado,Mariana Alvarenga Hoesen Doutel (2021)
Abstract Introduction: Bartter’s syndrome comprises a heterogeneous group of inherited salt-losing tubulopathies. There are two forms of clinical presentation: classical and neonatal, the most severe type. Types I and II account for most of the neonatal cases. Types III and V are usually less severe. Characteristically Bartter’s syndrome type IV is a saltlosing nephropathy with mild to severe neonatal symptoms, with a specific feature - sensorineural deafness. Bartter’s syndrome type IV is the least common of all recessive types of the disease. Description: the first reported case of a Portuguese child with neurosensorial deafness, polyuria, polydipsia and failure to thrive, born prematurely due to severe polyhydramnios, with the G47R mutation in the BSND gene that causes Bartter’s syndrome type IV. Discussion: there are few published cases of BS type IV due to this mutation and those reported mostly have moderate clinical manifestations which begin later in life. The poor phenotype-genotype relationship combined with the rarity of this syndrome usually precludes an antenatal diagnosis. In the presence of a severe polyhydramnios case, with no fetal malformation detected, normal karyotype and after maternal disease exclusion, autosomal recessive diseases, including tubulopathies, should always be suspected.